Histological Changes in the Rat Femoral Artery Following the Use of the Empty-and-Refill Test - Naides, Alexandra; Noland, Roberto; Lu, Jiajie G.; Akelina, Yelena; Marboe, Charles; Strauch, Robert J. (Journal of Reconstructive Microsurgery, 2018)
Background This study examines the effects of the empty-and-refill patency test on rat femoral arteries in the longer postoperative time period.Methods A simple arterial anastomosis was performed bilaterally on 20 rats. The empty-and-refill test was performed unilaterally in all rats, leaving the contralateral artery as an internal control. Rats were divided into two cohorts of 10 rats and survived for 48 hours and 2 weeks. Vessel patency was assessed prior to closing and immediately prior to sacrifice. The femoral arteries were harvested bilaterally and hematoxylin and eosin stains were performed. The femoral artery distal to the anastomosis in the region of the empty-and-refill test was histologically evaluated.Results All vessels were patent at the time of sacrifice. There was no statistical difference in the numeric scoring between the experimental and control vessels in the 48-hour cohort. Almost all vessels harvested at 48 hours showed endothelial cell loss distal to the anastomosis regardless of whether they underwent the empty-and-refill test. The only statistically significant difference in the 2-week cohort was an increase in adventitial smooth muscle proliferation in the experimental group. There were no other statistically significant results between the experimental and control groups at 2 weeks. An overall comparison of both cohorts revealed a statistically significant increase in endothelial cell number and intimal proliferation by 2 weeks postsurgery.Conclusion The empty-and-refill test does not compromise rat femoral artery anastomotic patency, nor does it produce histological damage either 48 hours or 2 weeks postsurgery.
Keywords: empty-and-refill patency test; thrombosis; microvascular surgery